Dopamine dynamics underlying maternal motivation and reward - Katherine R. Day; Stephen D. Shea (Neuroscience Research, 2025)
Maternal behavior comprises a diverse set of caregiving actions essential for ensuring offspring survival and development. Shaped by evolutionary pressures, these behaviors range from goal-directed and coordinated overt motor actions such as nest building and pup retrieval to sustained akinetic states such as nursing and crouching. These can each be thought of as varying along two continua, one which captures the appetitive versus consummatory aspects of a given behavior, and the other describes the relative activity or passivity of the behavior. Since individual behaviors (1) vary substantially along these axes, and (2) evolve in time, we propose that motivated execution of them is likely accomplished through dynamic regulation by multiple circuits and neuromodulatory systems. One important regulator of maternal behaviors is dopamine (DA), a key neuromodulator that makes diverse contributions to behavior. Classically, dopamine is hypothesized to play a role in both the appetitive (e.g. pup retrieval) and consummatory (e.g. nursing, grooming) aspects of maternal behavior via distinct circuitry. Considering recent studies revealing the temporal dynamics of DA during maternal behavior, we examine the complexity of the concepts of appetitive and consummatory drive as maternal behavior unfolds in time. We propose that seemingly discrete behaviors, like pup retrieval, may be appreciated as evolving sequences of appetitive and consummatory components that reflect shifts in underlying neural dynamics at different timescales.